Oral Advocacy Before the United States Supreme Court: Does It Affect the Justices' Decisions? - Timothy R. Johnson; James F. Spriggs II; Paul J. Wahlbeck (Washington University Law Review, 2007)
Our empirical investigation focuses on two areas. First, we are interested in the quality of the oral advocacy presented to the Court, especially in terms of its etiology, as well as its effectiveness. We investigate these questions empirically by utilizing notes taken by Blackmun during oral arguments while he sat on the Court. Specifically, we here utilize the grades that Justice Blackmun assigned to each attorney’s oral arguments. This information allows us to answer two related questions: (1) why do some attorneys make better arguments before the Court; and (2) does the quality of oral advocacy influence who wins and loses? Second, we turn our attention to the information the Justices elicit about themselves during oral arguments. We analyze data on how often Justice Blackmun paid attention to the views expressed by his brethren during oral arguments (by examining when and why he recorded the comments of a particular colleague during orals) and the factors that led him to pay attention to some, but not all, of his colleagues. Additionally, we utilize Blackmun’s notes to demonstrate that what transpired during oral arguments provided him with an indication of whether his colleagues would vote to affirm or reverse the lower court decision at issue. We do so through an examination of when Justice Blackmun attempted to predict the votes of his colleagues in his oral argument notes. The Article proceeds as follows. In the next two Parts, we take up our first set of questions, which focuses on whether experienced and resourceful attorneys provide better arguments and whether arguments presented by counsel can affect decisions Justices make. Part IV focuses on whether Justices attempt to learn about their colleagues during oral arguments and whether such information affects the coalition-formation process that follows the arguments. Finally, we analyze whether what transpires during oral arguments can help a Justice make predictions about how a case will ultimately be decided.
Keywords: Forensic orations; Appellate advocacy; Judicial process; United States. Supreme Court